(untitled) (Legal journal - Research in Legal and Social Sciences, 2021)
This research analyses the judicial criteria to determine a sentence, within the framework of art. 65, foundation for establishing a penalty, section 2, subsection 3, concerning the intensity of criminal energy. This foundation is set by a brief analysis of the background that gave origin to the criminal type, as criteria for quantifying the penalty. This research proves that the intensity of criminal energy is part of the reprobation as foundation for assessing the penalty. The interest is based on strong social complains expressed through the media in Paraguay, especially when certain cases gain traction, and much more in cases that ended with a nearly insignificant penalty, even when well known criminals are involved. This occurs fundamentally in homicide cases that have great impact on society, and as a consequence of this, an increasing feeling of insecurity in the population. This situation provokes society’s reaction by questioning judicial role, when judges release convicts with criminal records. Thus, the judge must evaluate the intensity of the energy, by assessing the active criminal behavior and omissions of the offender.